2020
DOI: 10.4018/978-1-7998-1851-9.ch008
|View full text |Cite
|
Sign up to set email alerts
|

Success Stories of ICT Implementation in Saudi Arabia

Abstract: Information and communication technology (ICT) has a great role in the development, growth, and economy of the country. ICT refers to any system, device, or product that can store, manipulate, and receive and transmit digital data effectively. ICT brings clear differences in the economy of countries wherever it is successfully implemented. It becomes a reason of timely, accurate, and efficient operations and becomes a source of user satisfaction by providing them fast, better, easy service around the clock. As… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 4 publications
0
29
0
Order By: Relevance
“…The MOH in Saudi Arabia has recently introduced additional features to the current TH services, which have been effectively incorporated into the provision of healthcare using mobile applications (e.g., Seha, Mawid, Tawakklna, Tabaud, and Tetamman) to cope with the pandemic,. [ 9 16 17 ] A cross-sectional survey on the knowledge, attitude, and practice of parents to TH mobile applications (e.g., Seha and Mawid) was recently conducted on 402 Saudi and non-Saudi parents. The study reported that 346/402 (86%) of the respondents acknowledged the potential benefits of these mobile applications, and had used them before to book appointments for their children.…”
Section: Telehealth In Saudi Arabiamentioning
confidence: 99%
See 2 more Smart Citations
“…The MOH in Saudi Arabia has recently introduced additional features to the current TH services, which have been effectively incorporated into the provision of healthcare using mobile applications (e.g., Seha, Mawid, Tawakklna, Tabaud, and Tetamman) to cope with the pandemic,. [ 9 16 17 ] A cross-sectional survey on the knowledge, attitude, and practice of parents to TH mobile applications (e.g., Seha and Mawid) was recently conducted on 402 Saudi and non-Saudi parents. The study reported that 346/402 (86%) of the respondents acknowledged the potential benefits of these mobile applications, and had used them before to book appointments for their children.…”
Section: Telehealth In Saudi Arabiamentioning
confidence: 99%
“…The COVID-19 pandemic has illustrated that TH is an excellent facilitator for care coordination and care delivery in Saudi Arabia. [ 9 10 ] However, TH services in Saudi Arabia are yet to reach expectation, and hence, there is a pressing need for the development of simpler and more interactive TH applications. [ 6 9 16 29 ] This development could be achieved by evaluating user satisfaction over time, ensuring that applications are being used properly,[ 30 ] and optimizing the design of the applications, taking into consideration cultural and behavior factors against the use of technology.…”
Section: Role Of Telehealth In Care Coordinationmentioning
confidence: 99%
See 1 more Smart Citation
“…To address this gap, the traditional centralized EL platform is not enough due to the limitations of limited transparency, low scalability, single point of failure and more vulnerable to security threats. Therefore, peer-to-peer EL platforms are better as they can easily accommodate the rapidly growing number of users (49,50) . A key reason for security threats in the EL platform is that more attention is given towards course development and delivery.…”
Section: Security and Privacy Issues In Elmentioning
confidence: 99%
“…Privacy and security issues linked to online applications could be effectively addressed using Blockchain. It is widely been used in various sensitive applications such as banking, business transactions and nowadays in education as well (49,54) . It is not a new technology rather a rearrangement of existing technologies deployed in a better way.…”
Section: Security and Privacy Issues In Elmentioning
confidence: 99%